Formation of 17-18 yrs age girl students' visual performance by means of visual training at stage of adaptation to learning loads - S.V. Bondarenko; N.O. Darzinska; L.V. Sіdilo (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: substantiation of health related training influence of basketball and volleyball elements on functional state of 1 st year students' visual analyzers in period of adaptation to learning loads with expressed visual component. Material: in experiment 29 students of 17-18 year age without visual pathologies participated. Indicators of visual performance were determined by correction table of Tagayeva and processed by Weston methodic. Accommodative function was tested by method of mechanical proximetry. Results: the authors worked out and tested two programs of visual training. Influence of visual trainings on visual performance's main components (quickness, quality, integral indicators) was studied as well as eye's accommodative function (by dynamic of position of the nearest point of clear vision). Conclusions: Application of visual trainings at physical education classes permits to improve indicators of visual analyzer's performance as well as minimize negative influence of intensive learning loads on eye' accommodative function.